Parental attachment and cyberbullying experiences among Malaysian children - Yusup, Sarina; Hassan, Md. Salleh; Abu Samah, Bahaman; Ibrahim, Muhamad Shamsul; Ramli, Nor Sabila; A. Rahman, Nur Atikah; Osman, Mohd Nizam (Universiti Putra Malaysia Press, 2018)
The purpose of this article is to illustrate the links between the three factors of parental attachment (i.e., communication, trust, and alienation) and cyberbullying experiences among school-going children. A total of 375 students aged 9 to 16 years old were selected using stratified sampling method from 8 schools in Selangor. The authors adapted a 10-item instrument from the previous studies of Youth Internet Safety Survey (YISS) and EUkidsonline scales to assess the cyberbullying prevalence based on two sub-dimensions (online harassment and sex-based bullying). The confirmatory factor analysis (CFA) was used to analyse the construct validity of the scales. Structural equation modelling (SEM) then was used to test the study hypotheses. The final model has an estimated that 10% (R2=.95) of the variance in cyberbullying is explained by parental attachment, indicating only the alienation factor predicted the children’s cyberbullying experiences. The findings, however, supported a differentiated approach to positive parenting.